Contemporary Buddhist Ethics. - Keown, Damien (Routledge critical studies in Buddhism., 2013)
This innovative volume brings together the views of leading scholars on a range of controversial subjects including human rights, animal rights, ecology, abortion, euthanasia, and contemporary business practice.